Günter Kunert: Sehnsucht nach Bomarzo. Reisegedichte. - Lisa Kahn (GDR Bulletin, 1979)
Leipzig: Reclam, 1978. 73 p. NOTE: Correct title for this work is Verlangen nach Bomarzo, under which it was published in both Germanies.